Laboratory experiments with self-cohesive powders: Application to the morphology of regolith on small asteroids. (1st November 2021) - Sánchez, Paul; Durda, Daniel D.; Devaud, Genevieve; Fischer, Alexander; Scheeres, Daniel J.; Dissly, Richard
Abstract: A series of experiments have been conducted to study the failure behavior of columns and piles comprised of cohesive fine powders in 1 ​g as a proxy for those which might occur in the agglomerated asteroid structure composed of cm-m size pebbles and boulders in a microgravity environment. Initially symmetrical piles of fine powders, under gravitation or centrifugal stress, develop features similar to those observed on asteroids, such as slide planes and finer cohesive structures. Failure of cohesive columns of fine powders occurs by the nucleation and propagation of fracture planes. In some cases, forming steep cliffs, also reminiscent of features observed on asteroids. Correlation between observed column failure and numerical simulations has been demonstrated based on preliminary results. Microstructure and particle size distribution are shown to substantially determine the extent of cohesiveness. Enhanced cohesion was observed for specific ratios of larger particle intermixed with fine powders. We propose that the wide range of qualitative features and behaviors may reasonably represent those observed on asteroid features as the surface ages. This work has important implications for our understanding and preparation for future missions to NEOs. Highlights: Cohesive powders under Earth's gravity are used as a proxy to study cohesive regolith on small asteroids. Piles of cohesive grains are formed and tilted until they collapse to evaluate their angle of repose. The talus of the collapsed piles formed cohesive clumps, akin to boulders on asteroids, which SFD has a −1.5 slope. Including larger grains in the cohesive piles reduced their angle of repose; this reflects a decreased cohesive strength.